The Inadequacy of Rawl’s Theory of Justice in the Face of Global Economic Interdependence - León Rojas, Alejandra (Pensamiento. Revista de Investigación e Información Filosófica, 2020)
The Theory of Justice by the North American philosopher John Rawls is considered one of the greatest contributions to the political philosophy of the twentieth century. On it, Rawls expressed his concern for a fair institutional order for all individuals. Therefore, he concentrates his efforts on justice, as the first virtue of social institutions, so that it goes across, on a domestic sphere, the basic structure of society and, in the international framework, relationships between States. This paper argues that the mentioned restricted version of society and the scope of justice, debts its theory against social differences in the countries’ life standards and the absolute poverty situation of several people in the world.
Keywords: Theory of Justice; distributive justice; economic interdependence; inequality